Promoting Mental Health and Wellbeing in Higher Education: a collaborative imperative / Dr. Farah Adilla Ab Rahman - Ab Rahman, Farah Adilla (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
The mental health and wellbeing of university faculty and students have become critical areas of concern in recent years. Depression, anxiety, stress, burnout, isolation, lack of support, an overwork culture, and a highly competitive environment are increasingly linked to careers in university education. These issues are exacerbated by growing pressures from university structures, increasing student numbers, diverse student needs, and the heavy burden of research (Hammoudi Halat, Soltani, Dalli, Alsarraj, & Malki, 2023). To counter these challenges, a collaborative effort at the organizational level is essential, with strategic initiatives aimed at leadership and implemented by faculty to promote their wellbeing.